Genome-Wide DNA Methylation and Transcriptome Analyses Reveal Epigenetic and Genetic Mechanisms Underlying Sex Maintenance of Adult Chinese Alligator - Lin, Jian-Qing; Yu, Jun; Sun, Li; Fang, Sheng-Guo (Frontiers in Genetics, 2021)
The sexes of Chinese alligators are determined during embryonic development and remain fixed thereafter. In this study, we investigated the genetic and epigenetic mechanisms underlying sex maintenance in Chinese alligators through RNA-sequencing and bisulfite sequencing data analyses of the adult gonads. We identified the genes and pathways (e. g., DMRT1-SOX9-AMH pathway for males and oocyte meiotic maturation pathway for females) involved in male and female sex maintenance and gonadal development of adult Chinese alligators. In contrast to their expression patterns in the embryo, both DMRT1 and the steroid hormone biosynthesis related genes showed a male-biased expression in adult gonads. The overall DNA methylation density and level were higher in testes than in ovaries. Hypermethylation in the gene bodies enhanced the expression of male-biased genes (such as DMRT1-SOX9-AMH and steroid hormone biosynthesis related genes) in the testis, as opposed to the normalization of gene expression. Our results provide insights into the genetic and epigenetic mechanisms underlying sex maintenance in adult Chinese alligators, and are expected to contribute to the development of scientific programs for the successful conservation of this endangered species.